Effect of the Window Position in the Building Envelope on Energy Consumption - Y. Azmy, Neveen; E. Ashmawy, Rania (International Journal of Engineering and Technology, 2018)
Windows play a significant role as they largely influence the energy load. Although there are many studies on the energy-efficient windows design, there is still a lack in information about the mutual impact of windows’ size, position and orientation on the energy loads. In this paper, the effect of different window positions and orientations on the energy consumption in a typical room in an administrative building that is located in the hot climatic conditions of Cairo city, Egypt is considered. This case study has been modeled and analyzed to achieve good environmental performance for architectural space, as well as assessing its impact on the amount of natural lighting required by using the Energy Plus program. The study concludes that the WWR (Window Wall Ratio) 20% square north-oriented upper  opening consumes 25% lower energy than the rectangular 3:1 opening in the lower west-oriented façade. The upper openings are the highest in terms of light intensity, as they cover about 50% of the room area. The WWR 30% rectangular north-oriented upper 3:1 opening consumes 29% lower energy than the rectangular lower 3:1opening in the façade. Regarding light intensity, the upper openings are the best for natural lighting as the light covers more than 60% of the room area.